Epigenetic targeting of autophagy for cancer prevention and treatment by natural compounds. (November 2020) - Vidoni, Chiara; Ferraresi, Alessandra; Secomandi, Eleonora; Vallino, Letizia; Dhanasekaran, Danny N.; Isidoro, Ciro
Abstract: Despite the undeniable progress made in the last decades, cancer continues to challenge the scientists engaged in searching for an effective treatment for its prevention and cure. One of the malignant hallmarks that characterize cancer cell biology is the altered metabolism of sugars and amino acids. Autophagy is a pathway allowing the macromolecular turnover via recycling of the substrates resulting from the lysosomal degradation of damaged or redundant cell molecules and organelles. As such, autophagy guarantees the proteome quality control and cell homeostasis. Data from in vitro, in animals and in patients researches show that dysregulation of autophagy favors carcinogenesis and cancer progression, making this process an ineluctable target of cancer therapy. The autophagy process is regulated at genetic, epigenetic and post-translational levels. Targeting autophagy with epigenetic modifiers could represent a valuable strategy to prevent or treat cancer. A wealth of natural products from terrestrial and marine living organisms possess anti-cancer activity. Here, we review the experimental proofs demonstrating the ability of natural compounds to regulate autophagy in cancer via epigenetics. The hope is that in the near future this knowledge could translate into effective intervention to prevent and cure cancer.